Low Threshold, High Efficiency Passively Mode-Locked Picosecond Tm,Ho:LiLuF4 Laser - Ling, Weijun; Xia, Tao; Sun, Rui; Chen, Chen; Xu, Qiang; Zhang, Yani (Frontiers in Physics, 2020)
We experimentally demonstrated a passively mode-locked picosecond Tm,Ho:LiLuF4 laser with low threshold and high efficiency. The stable continuous-wave (CW) mode-locked operation with 12ps pulse width is obtained by using a five-mirror cavity structure and semiconductor saturable absorber mirrors (SESAMs). The results indicate that the laser offers a mode-locked threshold power of 1.03W and maximum mode-locked output power of 350mW. The repetition rate of mode-locked pulse sequence is 98.04MHz, corresponding a maximum single pulse energy is 3.51nJ.